Conservation Genomic Analysis of the Croatian Indigenous Black Slavonian and Turopolje Pig Breeds - Lukić, Boris; Ferenčaković, Maja; Šalamon, Dragica; Čačić, Mato; Orehovački, Vesna; Iacolina, Laura; Curik, Ino; Cubric-Curik, Vlatka (Frontiers in Genetics, 2020)
A majority of nearly 400 existing local pig breeds are adapted to specific environments and human demands. Unfortunately, demand for large production quantities and industrialized pig production have caused rapid decline of many local pig breeds in the last few decades. Black Slavonian pig and Turopolje pig, the latter being highly threatened, are the two Croatian local indigenous breeds grown in typical extensive or semi intensive systems. We have analyzed their genetic diversity, inbreeding level and relationship with other local breeds across the world, modern breeds and several wild populations using high throughput genomic information (Illumina Infinium PorcineSNP60 v2 BeadChip). Multidimensional scaling analysis positioned Black Slavonian pigs close to the UK/North American breeds while Turopolje pig clustered within the Mediterranean breeds. A very high inbreeding level (FROH>4Mb=0.400 and FROH>8Mb=0.332), considerably exceeding the level of full sibs mating, has been observed in Turopolje pig while a much lower inbreeding (FROH>4Mb=0.098 and FROH>8Mb=0.074), indicating planned mating strategy, was observed in Black Slavonian. The results obtained reflect the current genetic status and breeding management of the two indigenous local breeds. While both breeds are very small, a controlled management activity has been implemented in Black Slavonian pigs since the market recognized its value. In contrast, the extremely high inbreeding level observed in Turopolje pig, warns for an urgent conservation plan with a long-term diversity-oriented breeding program.